Analisis Yuridis Putusan Bebas terhadap Pelaku Tindak Pidana Kekerasan Seksual terhadap Anak - Ulya Nadhira Putri; Dian Alan Setiawan (Bandung Conference Series: Law Studies, 2024)
ABSTRACT-Cases of sexual violence against children often occur in society. One form of criminal sexual violence is rape. Rape is when a man forces a woman to have sexual relations outside of marriage using violence. In criminal law, the act of rape is regulated in Book Two (II) Chapter the legal phenomenon under study. This research also uses a normative juridical approach. Normative juridical approach, namely a way of researching legal research carried out on library materials. This research aims to evaluate the judge's considerations in deciding cases in Decision Number 254/Pid.sus/2023/PN Mks) and to determine legal protection for child victims of sexual violence. The act of rape is regulated in Book Two (II) Chapter PN Mks is not quite right. ABSTRAK- Kasus pelecehan seksual mempengaruhi banyak anak di masyarakat, salah satu bentuk pelecehan seksual adalah penegakan hukum. Penelitian ini fokus pada penelitian hukum empiris dengan menggunakan KUHP dan pasal 35 Tahun 2014. Metodenya meliputi penjelasan rinci terhadap fenomena hukum yang diteliti dan menggunakan pendekatan yurisprudensi normatif. Kajian tersebut bertujuan untuk mengevaluasi potensi kerugian dari pelanggaran SK Nomor 254/Pid.sus/2023/PN Mks dan memahami dampak hukum terhadap anak yang mengalami pelecehan seksual.